1997
DOI: 10.1128/jcm.35.6.1327-1331.1997
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bartonella henselae and Bartonella clarridgeiae in stray cats

Abstract: The aim of the present work was to determine by blood culture the prevalence of blood infection with Bartonella species in a well-defined, European, urban stray cat population. Therefore, 94 stray cats were trapped from 10 cat colonies. Blood samples of these cats were cultured on both blood agar and liquid medium in order to raise the likelihood of bacterial detection. Fifty blood samples (53%) gave a positive culture result for Bartonella species. Isolate identification was performed by sequencing the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
3
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(90 citation statements)
references
References 30 publications
6
74
3
7
Order By: Relevance
“…In this study, more than half (62%) of the cats were bacteremic due to Bartonella spp. This infection rate is similar to those found in previous studies of stray cats (Table 3), which have reported prevalences of 22-59% [7][8][9]13]. Factors which appear to influence the prevalence of bacteremia include cat age, presence/absence of flea infestation, and the geographic region of the survey [6,8].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, more than half (62%) of the cats were bacteremic due to Bartonella spp. This infection rate is similar to those found in previous studies of stray cats (Table 3), which have reported prevalences of 22-59% [7][8][9]13]. Factors which appear to influence the prevalence of bacteremia include cat age, presence/absence of flea infestation, and the geographic region of the survey [6,8].…”
Section: Discussionsupporting
confidence: 89%
“…That the isolation of B. clarridgeiae was also achieved by this procedure may also be due to the release of this species from an intraerythrocytic location. Although kittens and young cats have been found to be more frequently bacteremic than older cats [7,9,24], a lack of perinatal transmission of B. henselae in experimentally infected cats has been demonstrated [25]. Transmission of B. henselae between cats has been demonstrated to occur through cat flea contact [25,26], and as transmission by flea bite was not observed in an experimental model, it is considered that B. henselae is excreted in flea feces and enters its host via broken skin associated with cuts or scratches [27].…”
Section: Discussionmentioning
confidence: 99%
“…For PCR amplification of the ribC gene, a set of primers ribC-F and ribC-R was used to amplify an expected 800-bp DNA fragment (Inoue et al, 2009). As the 16S rRNA gene has been well-accepted for species identification of bacteria, the primers P8 and Pc1544 were used for amplifying approximately 1300-1400 bp of the 16S rRNA gene (Heller et al, 1997).…”
Section: Dna Extraction and Polymerase Chain Reaction (Pcr) For Confimentioning
confidence: 99%
“…40 Another study showed that B henselae and B clarridgeiae bacteremia was found in up to 50% of the domestic and feral cat populations in regions where fleas were endemic. 41 However, B henselae infection was only documented by PCR assay in 2 of 117 (1.7%) community source cats used as blood donors in the United States. 32 Serologic cross-reactivity among B henselae and B clarridgeiae and B koehlerae does not always occur, but blood culture and PCR are capable of detecting all Bartonella species.…”
Section: Feline Diseasesmentioning
confidence: 99%